2009
DOI: 10.1007/s10823-009-9103-0
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Age Stereotypes and Self-Perception of Aging: A Comparison of French and Moroccan Populations

Abstract: The objective of this study was threefold: (1) assess the general perceptions of age stereotypes among older French and Moroccan adults, (2) analyze discourse associated with these different perceptions, and (3) compare aging self-perception scores of French and Moroccan (rural/urban) older adults and investigate the sociodemographic and health indicators likely to be associated with these self-perceptions. One-to-one structured interviews were conducted with 260 older French adults living in Marseille and 239… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
2
22
1
2
Order By: Relevance
“…For example, we found that women’s greater RRRs for high frequency of self-perceived uselessness disappeared when health and all other factors were modeled. This is consistent with several previous studies [47, 51], and is likely influenced by their traditional gender roles and their poor health compared to men [47]. Compared to respondents of minority ethnicity, Han older adults were more likely to report high frequency of self-perceived uselessness relative to low frequency, but there was no ethnic difference between moderate and low frequency.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For example, we found that women’s greater RRRs for high frequency of self-perceived uselessness disappeared when health and all other factors were modeled. This is consistent with several previous studies [47, 51], and is likely influenced by their traditional gender roles and their poor health compared to men [47]. Compared to respondents of minority ethnicity, Han older adults were more likely to report high frequency of self-perceived uselessness relative to low frequency, but there was no ethnic difference between moderate and low frequency.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, when young-old adults experience new negative events like illness, these problems can negatively impact their perceptions of usefulness in the absence of coping skills that develop over time [49]. Our findings for the fixed attribute of age are in line with one recent study that found no difference in self-perception of aging among the oldest-old aged 80 or older as compared to older adults aged 60–69 when health was controlled [51]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The idea is moreover also largely borne out by studies on (a) agerelated stereotypes, and (b) subjective well-being as well as adaptive self-regulation. Indeed, there is currently a relative consensus regarding age-related stereotypes in Western societies, and most researchers today concur that agerelated stereotypes are on the whole negative (e.g., Levy and Banaji 2002;Boduroglu et al 2006;Macia et al 2009;Palmore 2002). Yet, research on subjective well-being has shown it to vary little with age (for a review, see Diener and Suh 1998).…”
Section: Age Identity and Its Dimensionsmentioning
confidence: 99%
“…Pada orang dewasa yang mempunyai persepsi baik dikarenakan adanya kultur sosial yang baik dan gaya hidup yang masih tradisional atau rural. Sedangkan persepsi yang tidak cukup baik dikarenakan oleh gaya hidup urban dan telah menghilangkan nilai tradisional (Macia et al, 2009).Hubungan kecemasan dengan usia dewasa atau tua juga berkaitan dan ini ditemukan pada wanita premenopause dan wanita yang mendapat Hormon Replacement Terapy (HRT) serta wanita yang sudah menopause (Eum et al 2012).…”
unclassified